قياس ربح نشاط المرابحة في المصارف الإسلامية دراسة تطبيقية على مصرف الشام الإسلامي في سورية - العثمان محمد; الشيخ مروى يحيى (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهتم هذا البحث بدراسة نشاط المرابحة في المصارف الإسلامية الذي أخذ يغلب على أنشطتها التي تمارسها جبنا إلى جنب مع المصارف التقليدية، ونظراً لاختلاف صيغ التمويل والاستثمار المطبقة في المصارف الإسلامية؛ فقد يؤدي هذا لاختلاف أسس قياس الربح الناجمة عن تلك الأنشطة عما هو مطبق في المصارف التقليدية، لذا فقد يكون من الخطأ تطبيق الأسس المتبعة في المصارف التقليدية في مجال قياس الأرباح فيها. وهذا الأمر يستدعي ضرورة التعرف على ماهية المصارف الإسلامية والكيفية التي يتم من خلالها قياس نتائج أعمالها وذلك لتحافظ مهنة المحاسبة على دورها في تقديم المعلومات المفيدة لمتخذي القرار خاصة أن متخذي القرار في هذه المصارف لا يكتفون بمتابعة ومراقبة القدرة الكسبية بل هناك أهداف أخرى عديدة في ضوء التشريع الإسلامي. يهدف البحث بشكل أساسي إلى دراسة الجوانب المحاسبية والمعالجات المطبقة في إثبات ربح نشاط المرابحة في المصارف الإسلامية، من خلال بيان أسس احتساب التكلفة التي يتحملها العميل طالب شراء السلع في المصرف وكيفية تخطيط الأرباح في المصارف الإسلامية؛ وذلك بدراسة تطبيقية على مصرف الشام الإسلامي، ولتحقيق هدف الدراسة تم استخدام أسلوب دراسة الحالة حيث تم القيام بالزيارات الميدانية وإجراء العديد من المقابلات مع المسؤولين في المصرف، وقد توصل البحث إلى عدد من النتائج أهمها: تقاس عقود المرابحة بالتكلفة التاريخية مضافاً إليها المصاريف المباشرة المتعلقة بالعملية، يتم الاعتراف بالربح على أساس زمني متناقص، ولا يوجد أسس واضحة تحكم عملية تحديد نسب الربح لهذه العمليات. This research is interested in studying the activity of Murabaha in Islamic banks, which has become familiar in the activities of these banks, that operates its activities with conventional banks. And because of the different modes of finance and investment applied in Islamic banks, this may harm the bases of measuring the profit resulting from these activities than is applied in conventional banks. So it is wrong to apply the regulations of the conventional banks in the measurement of profit in it. This requires the need to identify how they are measuring the results of its operations and maintaining the accounting profession for its role in providing useful information to decision-makers, particularly as the decision makers in these banks do not just follow-up and monitoring capacity Acquisitivenesses, but there are other targets for many in Islamic law. The research aims mainly to study aspects of accounting and treatments applied in the proof of profit Murabaha activity in Islamic banks through the statement of calculating the cost borne by the client asked to buy goods in the bank and how to profit planning in Islamic banks. This has been achieved by studying the Application to al-Sham Islamic Bank. To achieve the objective of the study, situation study was used by the use of tools to examine the situation through interviews with officials at the bank. Then, the research has come to a number of important results: Murabaha contracts are measured by historical cost, plus the direct costs related to the transaction, profit is recognized on the basis of time-decreasing, and there is not any clear principles controlling the process of determining Profit rates for such operations.